Open Access Original Article The Best Imaging Modality for Axillary Lymph Node Status in Breast Cancer - Gul, Shandana; Azam, Zaini; Jan, Maria Mir; Tariq, Maham; Saleema, Aqsa; Naqvi, Syeda Rifaat Qamar (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To explore the diagnostic accuracy of different imaging modalities including Axillary Ultrasound (AUS), CT Scan and Contrast Enhanced Magnetic Resonance Imaging (MRI) breast in determining the axillary lymph node status in breast cancer keeping histopathology as reference standard. Study Design: Retrospective Comparative Study. Place and Duration of Study: The Breast Clinic, Combined Military Hospital, Rawalpindi Pakistan, from Jul 2022 to Jun 2023. Methodology: A retrospective comparative study was conducted at a dedicated breast cancer center with 90 early breast cancer patients. Diagnostic accuracy of Axillary Ultrasound, contrast-enhanced CT, and MRI was evaluated for axillary nodal staging. Final histopathology served as the reference standard. Imaging interpretations were performed by experienced radiologists, and data were analyzed using SPSS 22.0. The following metrics were determined: accuracy, specificity, negative predictive value, sensitivity, and specificity. Results: In total, 90 female patients mean age of 53.5±21.2 years were evaluated. N Staging displayed differences between patients who tested positive and negative for nodes. We found that MRI had the highest sensitivity of the three imaging modalities (93.34%: 95% CI, 84.34% - 98.82%) whereas CT scan had the lowest sensitivity (71.70%; 95% CI, 57.65% - 82.21). AUS had sensitivity (84.91%; 95% CI: 72.41% - 93.25) Similarly MRI had the highest Specificity of the three imaging modalities (78.38%: 95% CI, 61.79% - 90.17%) whereas CT scan had the lowest Specificity (62.96%; 95% CI, 42.37% -80.60%) and AUS had Specificity (67.57%; 95% CI: 50.21% - 1.99%). Conclusion: MRI scan is more effective; Axillary Ultrasound shows better outcomes than..